DESIGN OF NON-CRITICAL ITEM SUPPLIER SELECTION PROCEDURE USING FUZZY ANALYTICAL HIERARCHY PROCESS (FUZZY AHP) AND TRAFFIC LIGHT SYSTEM (TLS) METHODS - Rachmansyah Rizal Hidayat; Bambang Purwanggono; Arfan Bakhtiar (Universitas 17 Agustus 1945 Semarang, 2023)
Suppliers play an important role in determining product quality, costs, product development, and access to finance for companies. If the company is less selective in choosing its suppliers, the costs incurred may become ineffective. This study aims to develop or design a supplier selection model for non-critical items in Fast Moving Consumer Good companies. In this study, a literature review approach is used by examining 10 journals that have discussed supplier selection procedures. Each journal used as a basis for this study also has different problem objects, models, variables, methods and results. The results of the cross-reference analysis are used to design a procedural model for selecting suppliers for non-critical items. The design of the non-critical item supplier selection model uses several criteria which will later be used as the basis for selecting non-critical item suppliers. From several journals that have been studied, several criteria are obtained that are in accordance with the company that the researcher will conduct research, and will later be re-elected according to the company's needs. This study aims to develop or design a supplier selection model for non-critical items in FMCG (Fast Moving Consumer Good) companies. By using the F-AHP (Fuzzy – Analytical Hierarchy Process) and TLS (Traffic Light System) model, companies that have never had a procedure for selecting suppliers for non-critical items can carry out this procedure so that in the future this procedure can become a standard in companies in terms of choosing supplier.